Jane Tolmach for Assembly, 36th District letter - Jane Tolmach:::::: (1976)
In a May 21, 1976 campaign letter to "Dear Fellow Democrat," Jane Tolmach urged support for her candidacy in the 36th Assembly District seat being vacated by Ken MacDonald. She highlighted her experience in local government, including service on a school board, city council, and as mayor, and expressed her intention to seek a leadership role in the Assembly. Citing the California Journal, she described the race as a key district and noted that her campaign was considered the favorite to win. Tolmach emphasized her strong fundraising events, broad organizational endorsements, and backing from prominent Democratic legislators. She concluded by asking for volunteers and contributions to secure a decisive primary victory and retain the seat in November.